What should a Judiciary Administrator do to Monitor the ManagerEmployees Relationship? Evidence from a Sample of Tunisian Confiscated Companies - Abdelali Bahri; Faten Zoghlami (Journal of Accounting, Business and Management (JABM), 2023)
Using Churchill's paradigm and the principal components analysis, this paper aims to specify the main tasks that should include an effective judiciary administrator mission to monitor the employee-manager relationship in the context of a sample of Tunisian confiscated firms. Findings revealed two main sets of tasks. The first set is composed of specific tasks that would permit monitoring the conflicting manager-employees relationship, as established by the agency theory. The second set highlights tasks that would permit to monitor eventual manager-employees complicit relationship and which may favor the manager entrenchment. Our findings would contribute to the debate concerning the judiciary administrator performance determinants. Especially, it would help practitioners and regulatory instance to rethink and to redefine tasks that should include an efficient judiciary administration mission. Our paper would also, contribute to the existing literature which seems silent regarding this issue dealing especially with the judiciary administrator mission and the confiscated companies.